PPK: MENUMBUHKAN MINAT WIRAUSAHA MAHASISWA DI INSTITUT SAINS & TEKNOLOGI AKPRIND YOGYAKARTA - Muhammad Yusuf; Beny Firman (IST AKPRIND Yogyakarta, 2018)
PPK (Entrepreneurship Development Program) is a scheme of Community Service programs from the Ristekdikti managed nationally through DRPM with the aim of fostering entrepreneurship programs among campuses. With this activity, students can hone the entrepreneurial spirit, improve soft skills by being directly involved in the world of work, increasing the courage to start a business and get support in integrated mentoring. The existence of this KDP program is expected to be part of the community that can create jobs, reduce unemployment and become a change agent for community life that is more empowered and useful. The output of this activity is the training that can increase the capacity of tenants (students) in the field of entrepreneurship and the improvement of product quality for tenant businesses. The results obtained from the PPK activities at the AKPRIND Yogyakarta Institute of Science & Technology in 2018 were successfully in charge of the birth of 8 tenants as new entrepreneurs 1) VALHALLA GEOSERVICE: Thin section petrography preparation services and earth sample analysis as an effort to capture minimal long-term geopreneurship business opportunities competitors in Yogyakarta for students of geological engineering, 2) Courses in